210 Pb dating of the Miaoergou ice core from the eastern Tien Shan, China. Issue 66 (2014) - Wang, Chaomin; Hou, Shugui; Pang, Hongxi; Liu, Yaping; Gäggeler, Heinz W.; Tobler, Leonhard; Szidat, Sönke; Vogel, Edith
Abstract: In 2005, two ice cores with lengths of 58.7 and 57.6 m respectively to bedrock were recovered from the Miaoergou flat-topped glacier (43°03′19″ N, 94°19′21″ E; 4512 m a.s.l.), eastern Tien Shan. 210 Pb dating of one of the ice cores (57.6 m) was performed, and an age of AD 1851 ± 6 at a depth of 35.2 mw.e. was determined. For the period AD 1851-2005, a mean annual net accumulation of 229 ± 7 mm w.e. a– 1 was calculated. At the nearby oasis city of Hami ( 80 km from the Miaoergou flat-topped glacier) the annual precipitation rate is 38 mm w.e. a– 1, hence glacial meltwater is a major water supply for local residents. The surface activity concentration of 210 Pbex was found to be 400 mBq kg– 1, which is higher than observed at other continental sites such as Belukha, Russia, and Tsambagarav, Mongolia, which have surface activity concentrations of 280 mBq kg– 1 . The 210 Pb dating agrees well with the chronological sequence deduced from the annual-layer counting resulting from the seasonalities of d 18 O and trace metals for the period AD 1953-2005, and ^ -activity horizons resulting from atmospheric nuclear testing during the period AD 1962-63. We conclude that 210 Pb analysis is a suitable method for obtaining a continuous dating of the Miaoergou ice core for 160 years, which can also be applied to other ice cores recovered from the mountains of western China.